Weed Management in Ajwain (Trachyspermum ammi L.) at Farmer’s Fields in South East Rajasthan - Meena, R. P.; Hargilash; Ram, Mani; Sharma, R. N. (International Journal of Bio-resource and Stress Management, 2023)
The field experiments were conducted during kharif (July–October) seasons of 2014–15 and 2015–16 at KVK, Rajsamand, Rajasthan and farmers’ field with objective to explore and test other alternative and economical methods of weed control. On-farm Trial, technology option Oxadiargyl applied 50 g a.i. ha-1 applied as early post emergence at 20 DAS proved the best over farmers’ practice as well over recommended practice of 1.0 kg a.i. ha-1 pendimethalin pre-emergence in terms of growth and yield attributing characters viz., plant height, primary and secondary branches, number of umbels, number of umbellets umbel-1, number of seeds umbel-1 and remained statistically at par with weed free treatment. Weed indices namely weed count, weed dry weight, weed index and weed control efficiency were statistically significant by oxadiargyl applied 50 g a.i. ha-1 as early post emergence at 20 DAS and pre-emergence application of pendimethalin 1.00 kg a.i. ha-1 pendimethalin over farmer’s practice. Lower WI and higher WCE was observed by oxadiargyl applied 50 g a.i. ha-1 followed by pendimethalin 1.00 kg a.i ha-1. Grain and starw yield recorded in weed free plot was statistically at par with yield obtained by application of oxadiargyl 50 g a.i. ha-1. Net returns and B:C were also high in refined technology option i.e. of 50 g a.i. ha-1 oxazdiargyl (` 127570 ha-1 and 4.77) over recommended practice of 1.0 kg a.i ha-1 pendimethalin pre-emergence (` 107930 ha-1 and 4.19) and farmers’ practice (` 75930 ha-1 and 3.49).